Development Of Thematic Teaching Materials Based On Local Ceremony In Theme 5 "My Experience" Class 2 SD / MI - Mardiah Astuti; Hani Atus Sholikhah; Alfina Fitriyantica (AIUA Journal of Islamic Education, 2020)
The research method used is a research and development method with a model developed by Tessmer named formative evaluation which consists of 5 stages: self evaluation, expert review, one-to-one evaluation, small group evaluation, and field test. This study aims to: (1) produce teaching materials based on local wisdom theme 5 sub-themes 4 class II SD / MI, (2) test the teaching materials based on local wisdom themes 5 sub-theme 4 class II SD / MI in the form of validation, (3) testing the teaching material based on local wisdom theme 5 subtheme 4 grade II SD / MI in the form of practicality, and (4) testing the teaching material based on local wisdom theme 5 subtema 4 grade II SD / MI in the form of effectiveness. Data collection used is documentation, questionnaires, and tests. The data validation test uses a questionnaire at the expert review and one-to-one evaluation stages. The practicality test of the data uses a questionnaire at the small group evaluation stage, while the effectiveness test uses tests and field tests. The subjects of this study were students of class II 143 primary school Palembang with a total of 31 students. The results showed that teaching materials based on local wisdom on the theme of 5 subtheme 4 class II were categorized as valid, practical, and effective. This can be seen from (1) evaluation of the results of the validation questionnaire at the stage of expert review and one-to-one evaluation with an average score of 92 so that it is categorized as very valid, (2) assessment of practicality questionnaire at the small group evaluation stage with an average score 94 so that it is categorized as very practical, and (3) an assessment of the effectiveness of the test results at the field test stage with an average score of 87 so that it is categorized as very effective.